First record of genus Lakshmia Yakovlev, 2004 from India along with description of a new species (Lepidoptera: Cossidae, Zeuzerinae) - Navneet Singh; Jalil Ahmad; Roman V. Yakovlev; Rahul Joshi (SHILAP, 2024)
The present manuscript deals with description of a new species of genus Lakshmia Yakovlev, 2004, Lakshmia narayani Singh, Ahmad, Yakovlev & Joshi, sp. nov. is described from specimens of Mizoram, India. This also represents the first record of genus Lakshmia from India. Images of the adult and genitalia along with a complete checklist of the species is also provided.